(3GdCQL aj GdaQLs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GHf CHj GdOfjG , CHh HcQ YHO Gddg Hf eMeO Hf YHjO Hf SajGf GHf CHj GdOfjG GdbQTj GdCehj,J (B281 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hGdMeO ddg QH GdYGdejf gPG JCdja dWja dNUJ ajg cJGH GdaQL HYO GdTOI dCHi HcQ Hf CHj GdOfjG eY RjGOGJ MSfI hSejJg HGdCQL ai GdaQL s
(3BNQgG (B:s
(3hGUHQ aEf GdUHQ ai GdOfjG Edi fjd GdefG hGdbUO fYe GdefgL JeJ hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds